“Messing with the mind”: evolutionary challenges to human brain augmentation - Saniotis, Arthur; Henneberg, Maciej; Kumaratilake, Jaliya; Grantham, James P. (Frontiers in Systems Neuroscience, 2014)
The issue of brain augmentation has received considerable scientific attention over the last two decades. A key factor to brain augmentation that has been widely overlooked are the complex evolutionary processes which have taken place in evolving the human brain to its current state of functioning. Like other bodily organs, the human brain has been subject to the forces of biological adaptation. The structure and function of the brain, is very complex and only now we are beginning to understand some of the basic concepts of cognition. Therefore, this article proposes that brain-machine interfacing and nootropics are not going to produce “augmented” brains because we do not understand enough about how evolutionary pressures have informed the neural networks which support human cognitive faculties.